(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1991)
Spectral analysis technique has been applied for the first time in the Southern Alps, to three pelagic and hemipelagic sections (Venetian Prealps and Dolomites) of Barremian-Cenomanian age, characrerized by a couplet alternation of carbonate rich and carbonate poor layers. This technique is used to detect these lithologic periodicities in the measured sections, in order to search for climatic Milankovitch-type cycles (short eccentricity, obliquity and precession cycles). We have applied two different processing routines: the FFT algorithm has been developed to process, for example, bed thickness, bed-joint position and calcimetric time series; for the other cases rhe FWT algorithm has been used to deal with a codified time series, such as lithotype signals or the presence/absence of some bioturbation signal. The results of the data processing are amplitude and power spectra, showing frequency peaks with maximum energy. They are computed first in terms of space measurements (cm) and later are converted into time (thousand of years) using the average sedimentation rate, inferred for each section by the duration of stratigraphic units (stages) and their thickness in the studied section. To prevent distortion related to the form of the input signal a smoothed triangular filter of different length was used, as a way of obtaining a sinusoidal-like wave. The stability of the most relevant peaks can be tested by dividing the original time series into two or more subsections. They are then processed by sample rates to generate spectra with different resolution levels.